Vpliv gostote prometa in načina vožnje na prometni tok ter izpuste CO2 - Rigler, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2024)
The purpose of the article is to study the traffic characteristics on a 1500 m long road with one lane and to find out how the flow and carbon dioxide (CO2) emissions are affected by the density of vehicles, the speed limit, and the way of driving. The research uses a microscopic cellular automaton traffic model (hereafter CA), called the extended LAI model, which contains new functions and is upgraded for the calculation of discharges. Based on the results of traffic simulations, CO2 emissions per kilometre driven were calculated using the model presented by Panis, Broekx and Liu (2006). The results show that the maximum flow of 2122 vehicles/hour is achieved at a maximum speed of 70 km/h and a density of 0.25 vehicles/cell. Between densities of 0.22 and 0.28 vehicles/cell, the traffic flow is in a synchronized phase, with the average speed dropping due to vehicle interaction. At higher densities, congestion occurs, the average speed continues to fall, and the amount of emissions increases. The top speed only affects CO2 emissions at lower densities, but at higher densities, they are much more affected by the acceleration rate. We believe that it would be beneficial to reduce traffic density in times of traffic congestion to achieve the most optimal flow and reduce negative impacts on the environment, for example by encouraging occasional work from home, use of public transport, and trips before or after the expected traffic peaks.
Keywords: avtomobilski promet; cellular automata; cestni promet; CO2 emissions; emisijski modeli; emission models; extended LAI mode; flow models; izpusti CO2; microscopic traffic; prometni tokovi; traffic flow; varstvo okolja